Koordinasi Pengawas dan Kepala Madrasah dalam Meningkatkan Prestasi Kerja Guru MIN 1 Aceh Tenggara - Ahmad, Sabaruddin (Prodi PAI STAI Sumatera Medan, 2020)
This paper aims to analyze the implementation and obstacles in coordination between supervisors and madrasah principals in improving the work performance of MIN 1 Aceh Tenggara teachers. The focus of this research discussion is the form of coordination, implementation, and coordination barriers between supervisors and principals of the madrasah. This research uses a qualitative approach with a descriptive-analytic method. Data collection was carried out by interviewing the participants of the MIN 1 Aceh Tenggara Teachers, and observation and documentation techniques. Furthermore, the data were analyzed using data reduction techniques, data presentation, and drawing conclusions. The validity of the data was tested by means of triangulation, both methods and sources. The results of this study indicate that (1) the form of coordination between supervisors and principals of madrasah is in the form of an annual program of activities on teacher performance; (2) The coordination includes observation and class visits, supervision meetings and teacher training; and (3) obstacles in coordination, namely competition for the quality of madrasah ibtidaiyah with basic education institutions at the same level (SD-IT, SD, and other similar institutions).